Pieces of the puzzle - Trait Information Portal - Dias, S. (PGR secure, 2012)
The need to have a portal to access complementary data on traits is essential and a novelty arising from the PGR Secure project. Further, until now we have been able to access online many resources for ex situ information, but very few for in situ and on-farm information. This article focuses on one of the tasks of the PGR Secure informatics work package; namely, the development of a Trait Information Portal (TIP). The TIP envisaged will provide a unique entry point for the breeder community to access trait-specific information to help direct their research and allow them to obtain germplasm of CWR and LR for their breeding programmes.